Development of contextual teaching and learning based audiovisual learning videos in III grade of elementary school - Noviana, Dian; Rosidin, Odien; Yuliana, Rina (Universitas Nusantara PGRI Kediri, 2023)
This research aimed to determine the development and feasibility of audiovisual learning videos based on the Contextual Teaching and Learning (CTL) approach, as well as to assess the students' response to the audiovisual learning videos on the topic of food technology. The method used in this research is Research and Development (RnD) from Borg & Gall. This development only used 6 steps out of 10 steps, this is because researchers only conduct research at one educational institution (school) and see the limited time, effort, and costs of researchers. Product assessment for the feasibility test of contextual teaching and learning based audiovisual learning videos was carried out by 3 experts, namely a media expert, language expert, and subject matter expert with the target of limited-scale product trials, that are students of class IIIB MIN 1 Tangerang City, totaling 30 people. The results of the feasibility assessment after validation by the experts are as follows: (a) media validation scored 80%; (b) language validation scored 82%; and (c) subject matter validation scored 76.5%. Consequently, the overall feasibility score for the audiovisual learning videos was 79.5%, indicating that the videos are considered